Ролевая игра как средство обучения иноязычной лексике детей дошкольного возраста - Каменский, А.И.; Каменская, И.Б. (Культура народов Причерноморья, 2003)
The article dwells upon the problem of teaching pre-school children English vocabulary. Situation-based role-plays are suggested as a complex of activities to attain rational methodological organisation of the teaching process. Activities are sequenced in three stages, combined as a series of lessons on a separate topic. Illustrative examples and recommendations on conducting lessons are provided.